(untitled) (Research, Society and Development, 2023)
Hemophilia is an alteration related to genes, hemorrhagic, and of recessive inheritance, affecting only male members, resulting from modifications in the fundamental units of heredity, encoding factors VIII (hemophilia A) or IX (hemophilia B) of coagulation, located on the long arm of the X chromosome contained in blood plasma responsible for the complex sequence of chemical reactions that result in the formation of a fibrin clot. The objective of the inquiry was to argue the vast reference that deals with the presence of hemophilia in the face of the diagnostic, laboratory, therapeutic and outpatient approach. This is a narrative review composed of 21 articles, using the descriptors "Hemophilia" and "Treatment". It is concluded that Hemophilia type A and B is a disease that has been extensively investigated over time, however it involves numerous highly complex contextualizations that need to be considered and the laboratory analyzes used for the investigation and monitoring of hemophilia, promote conjectures limited, given the complications of quantifying low levels of antibodies.